Shallow magmatic processes revealed by cryptic microantecrysts: a case study from the Taupo Volcanic Zone - Lormand C; Zellmer GF; Sakamoto N; Ubide T; Kilgour G; Yurimoto H; Palmer A; Németh K; Iizuka Y; Moebis A (Springer Nature, 2021)
Arc magmas typically contain phenocrysts with complex zoning and diverse growth histories. Microlites highlight the same level of intracrystalline variations but require nanoscale resolution which is globally less available. The southern Taupo Volcanic Zone (TVZ), New Zealand, has produced a wide range of explosive eruptions yielding glassy microlite-bearing tephras. Major oxide analyses and textural information reveal that microlite rims are commonly out of equilibrium with the surrounding glass. We mapped microlites and microcrysts at submicron resolution for major and trace element distributions and observed three plagioclase textural patterns: (1) resorption and overgrowth, (2) oscillatory zoning, and (3) normal (sharp) zoning. Pyroxene textures are diverse: (1) resorption and overgrowth, (2) calcium-rich bands, (3) hollow textures, (4) oscillatory zoning, (5) sector zoning, (6) normal zoning and (7) reverse zoning. Microlite chemistry and textures inform processes operating during pre-eruptive magma ascent. They indicate a plumbing system periodically intruded by short-lived sub-aphyric dykes that entrain microantecrysts grown under diverse physico-chemical conditions and stored in rapidly cooled, previously intruded dykes. Changes in temperature gradients between the intrusion and the host rock throughout ascent and repeated magma injections lead to fluctuations in cooling rates and generate local heterogeneities illustrated by the microlite textures and rim compositions. Late-stage degassing occurs at water saturation, forming thin calcic microcryst rims through local partitioning effects. This detailed investigation of textures cryptic to conventional imaging shows that a significant proportion of the micrometre-sized crystal cargo of the TVZ is of antecrystic origin and may not be attributed to late-stage nucleation and growth at the onset of volcanic eruptions, as typically presumed.
Keywords: Microcrysts; Tongariro volcanic centre; Chemical zoning; Intermediate magmas; Magma ascent